Effects of land use and climate change on functional and phylogenetic diversity of terrestrial vertebrates in a Himalayan biodiversity hotspot. (29th July 2022) - Penjor, Ugyen; Cushman, Samuel A.; Kaszta, Żaneta M.; Sherub, Sherub; Macdonald, David W.
Abstract: Aim: The synergy between human land use and climate change is accelerating the global decline of biodiversity. In the fragile Himalayas, this trend has a strong ecological impact on wildlife communities, and a better understanding is needed to discern changes in the mechanisms. This study aims to understand the effects of land use and climate change on the functional (FD) and phylogenetic diversity (PD) of mammal and bird communities across the land use gradient. Location: Eastern Himalayan biodiversity hotspot, Bhutan. Methods: Mammal data were gathered from a camera trap survey and bird data from point counts. We used morphological and ecological traits of 45 mammal species and 336 bird species to construct functional trait space. We quantified FD and PD using standardized effect size of functional richness, functional dispersion, mean pairwise distance and mean nearest taxon distance. We used linear regression to evaluate the relationship between FD and PD and land use/climate variables. Results: The functional space of mammals was structured by body mass (small–large) and diet (herbivore–carnivore) as one major axis, and habitat breadth (generalist‐specialist) as the other, whereas bird functional space was structured by beak shape and size (large and long–small and short), body mass (small–large), foraging strata (canopy–ground) and diet (ectotherm–scavenge) along four axes. Land use (agriculture and road) negatively affected mammal FD, whereas both land use (tree cover and built‐up area) and climate (temperature and precipitation) affected PD, although the effects were highly variable. Climate (temperature) had a pronounced negative effect on bird FD while land use (agriculture, built‐up area and settlement) on PD. Main conclusions: The realized functional space of the vertebrate groups can be represented by different planes on which species are clumped around a small number of functional strategies. The loss of species at the edge of functional space is non‐random and could result in the loss of irreplaceable traits impacting long‐term ecological and evolutionary processes. Our study demonstrates the filtering effect of anthropogenic pressure and climate change on vertebrate FD and PD. However, the association with land use suggests the potential for ecosystem services (particularly by birds). Our findings reveal nuances of dimensions of biodiversity and provide novel insights into the structure and drivers of vertebrate assemblages in the eastern Himalayas.